'Guests': Three migrant voices in Italy. (August 2015) - Portelli, Alessandro
This article explores the different ways in which migrants in Italy use music to comment on their marginalized condition. By modifying the lyrics of Freddie Aguilar's hit song 'Anak, ' Camilo Cosmecio, a Filipino hotel cleaner, turns a song about generational conflict into one that conveys a migrant's ache for a faraway son. In his self-penned song 'Istaranyieri baan ahai' (I am a foreigner), Somali Geedi Yusuf Kuule uses ironically the word osbitaan, a migrant's mispronunciation of ospite (guest): a hypocritical word which, far from signifying hospitality, denies a migrant the chance to become integrated into the host culture and be treated as a citizen with rights. Migrant music is today an essential part of the folk music of Italy. Like Italy's own emigration songs, this 'foreign' (African, Slavic, Indian) music is the voice of the excluded singing about their plight. It is about hurt, loneliness, abandonment; and in some cases about the dream of a life led not as permanent 'guests, ' but as equal and active members in a shared society. This has been the uniquely joyful experience of Jagjit Rai Mehta, an Indian stable hand on an industrial farm in Piadena (Po Valley), who welcomes Italians and foreigners to a place that is now his home.